The Principal Strategy In Developing Teacher Professional Competence In Islamic Junior High School Al-Jam'iyatul Washliyah Tembung, Deli Serdang District - Handoko Handoko (LPPPIPublishing, 2021)
This study is to describe how the principal's strategy for developing teacher professional competence at Islamic Junior High School Al- Jam'iyatul Washliyah Tembung, Deli Serdang Regency, is one way to develop the quality of teacher professionalism and achieve educational goals. The type of research used is a type of qualitative research with a naturalistic approach. Collecting research data obtained by observation, interviews, and documentation studies. The data analysis step is to collect data, reduce the data and then conclude the data. To test the validity of the data, credibility, transferability, dependability, and confirmability were carried out. The findings of this study reveal three related findings: 1) Principal's strategy towards teacher professional competence development in Islamic Junior High School Al- Jam'iyatul Washliyah Tembung 2) The principal's actions on teacher professional competence development programs in Islamic Junior High School Al- Jam'iyatul Washliyah Tembung 3) Supporting factors and inhibiting factors for the development of teacher professional competence in Islamic Junior High School Al- Jam'iyatul Washliyah Tembung. The results of this study concluded that the principal's strategy for developing teacher professional competence at Islamic Junior High School Al- Jam'iyatul Washliyah Tembung was carried out well and continued to improve to achieve better goals in the future